2007
DOI: 10.1016/j.jmwh.2007.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Certified Nurse Midwife‐Attended Births: Trends in Washington State, 1995–2004

Abstract: Nationwide, the proportion of certified nurse-midwife (CNM)-attended births has increased steadily. We examined trends in CNM-attended singleton spontaneous vaginal births between 1995 and 2004 in Washington State by site of birth, payer source, and hospital birth volume. CNMs were more likely than other providers to care for women at risk for adverse outcomes based on several sociodemographic indicators. The increased rate of CNM-attended births occurred primarily in hospitals and among both Medicaid- and pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Similar findings were reported by Clark et al in 1997 . A study of Washington state birth certificate data (1995‐2004) found more women with Medicaid and fewer women with private insurance attended by midwives compared to physicians . However, broad changes have occurred since the 1990s, including adoption of an updated (2003) birth certificate data collection and reporting form, the rise of managed care, consolidation and regionalization of perinatal care, nationwide demographic shifts, and increasing rates of midwife‐attended births in and out of hospitals …”
Section: Literature Reviewmentioning
confidence: 99%
“…Similar findings were reported by Clark et al in 1997 . A study of Washington state birth certificate data (1995‐2004) found more women with Medicaid and fewer women with private insurance attended by midwives compared to physicians . However, broad changes have occurred since the 1990s, including adoption of an updated (2003) birth certificate data collection and reporting form, the rise of managed care, consolidation and regionalization of perinatal care, nationwide demographic shifts, and increasing rates of midwife‐attended births in and out of hospitals …”
Section: Literature Reviewmentioning
confidence: 99%